Reconstructing the Oversight System for Public Procurement in Indonesia: A Legal and Normative Analysis of Corruption Prevention - Mujahidin Mujahidin; Amir Ilyas; Marwati Riza; Aswanto Aswanto; Muhammad Mutawalli Mukhlis (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2026)
The oversight system established under Presidential Regulation No. 16 of 2018 aims to facilitate the achievement of public procurement objectives. However, challenges remain in realizing these objectives due to legal non- compliance among stakeholders, as evidenced by the high level of corruption in public procurement. This research investigates the reconstruction of the oversight system for public procurement in Indonesia. Using a normative legal research method, the study focuses on analyzing and interpreting legal norms, principles, and their impact on society. The research examines the legal framework governing public procurement, including the systematic arrangement of regulations, synchronization between laws, historical developments, and comparisons with oversight systems in other jurisdictions. The findings reveal that the oversight of public procurement is regulated under Presidential Regulation No. 16 of 2018, where the Inspectorate of Government Internal Supervisory Apparatus (GISA) is responsible for initial investigative oversight. If indications of corruption are found, GISA refers the case to Law Enforcement Agencies (LEA) for further investigation. GISA's role is embedded in risk management to prevent corruption, while the Corruption Eradication Commission (CEC) highlights key preventive measures. This study emphasizes the need for stronger synchronization between regulations and enhanced risk management strategies to ensure effective oversight of public procurement.